Dural Immune Cells, CGRP, and Migraine - Balcziak, Louis K.; Russo, Andrew F. (Frontiers in Neurology, 2022)
Migraine is the most common neurological disorder in the world, affecting 12% of the population. Migraine involves the central nervous system, trigeminal nerves and meninges. Recent advances have shown that targeting calcitonin gene-related peptide (CGRP) through either antibodies or small molecule receptor antagonists is effective at reducing episodic and chronic migraine episodes, but these therapeutics are not effective in all patients. This suggests that migraine does not have a singular molecular cause but is likely due to dysregulated physiology of multiple mechanisms. An often-overlooked part of migraine is the potential involvement of the immune system. Clinical studies have shown that migraine patients may have dysregulation in their immune system, with abnormal plasma cytokine levels either during the attack or at baseline. In addition, those who are immunocompromised appear to be at a higher risk of migraine-like disorders. A recent study showed that migraine caused changes to transcription of immune genes in the blood, even following treatment with sumatriptan. The dura mater is densely packed with macrophages, mast and dendritic cells, and they have been found to associate with meningeal blood vessels and trigeminal afferent endings. Recent work in mice shows activation and morphological changes of these cells in rodents following the migraine trigger cortical spreading depression. Importantly, each of these immune cell types can respond directly to CGRP. Since immune cells make up a large portion of the dura, have functional responses to CGRP, and interact with trigeminal afferents, CGRP actions on the dural immune system are likely to play key roles in migraine.